Method for producing hydrophilic film and substrate with hydrophilic surface

By polymerizing specific monomers on the base material surface and reacting them with zwitterionic reactants, a durable and thick hydrophilic film is achieved, addressing the limitations of existing methods and enhancing the material's hydrophilicity and durability.

JP7605435B2Active Publication Date: 2024-12-24DAINICHISEIKA COLOR & CHEMICALS MFG CO LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021156934
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-27
Publication Date
2024-12-24
Estimated Expiration
2041-09-27

AI Technical Summary

Technical Problem

Existing methods for creating hydrophilic films on base materials face challenges due to the solubility of hydrophilic group-containing monomers in water-based solvents, limiting polymerization methods and resulting in films with insufficient durability and thickness.

Method used

A method involving the polymerization of monomers like dimethylaminoethyl methacrylate and dimethylaminopropyl methacrylamide on the base material surface, followed by reaction with specific reactants to form a hydrophilic film with zwitterionic groups, using surface-initiated living radical polymerization under high pressure to achieve a thick and durable hydrophilic layer.

Benefits of technology

The method enables the formation of a hydrophilic film with excellent durability and thickness, exhibiting properties such as high elasticity, ultra-low friction, and size exclusion, suitable for various applications including medical components and electronic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605435000001
    Figure 0007605435000001
  • Figure 0007605435000002
    Figure 0007605435000002
  • Figure 0007605435000003
    Figure 0007605435000003
Patent Text Reader

Abstract

To provide a method for producing a hydrophilic film that can readily form a hydrophilic film having sufficient thickness and excellent hydrophilicity on the surface of a substrate.SOLUTION: A method for producing a hydrophilic film includes the steps of: polymerizing a monomer such as dimethylaminoethyl methacrylate, forming a polymer (i) having a structure represented by the general formula (1) and bound to a substrate surface, and providing a precursor polymer layer on the substrate surface; and reacting a reaction agent such as sodium chloroacetate with the polymer (i), forming a polymer (ii) having a zwitterionic group, and providing a hydrophilic film on the substrate surface, with the precursor polymer layer having a thickness of 500-3,000 nm. (A denotes O or NH, R1 denotes a hydrogen atom, a methyl group, an acyl group or the like, R2 denotes a methyl group or the like, Polymer (i) denotes the polymer (i), * denotes a position of bonding to the substrate surface).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a hydrophilic film, and a substrate having the hydrophilic film. [Background technology]

[0002] As a method for modifying a substrate, a method is known in which a polymer having a group at its end capable of adsorbing or reacting with the substrate is applied to the substrate to form a physically or chemically bonded polymer layer on the substrate surface. Also known is a method in which a polymerizable group provided on the substrate surface is used as a starting point to polymerize a monomer to form a grafted polymer layer from the substrate surface.

[0003] In recent years, so-called "concentrated polymer brushes" have been studied, which are densely grafted onto a substrate using the technology of living radical polymerization developed in the 1990s. In these concentrated polymer brushes, polymer chains are grafted onto the substrate at high density with intervals of 1 to 4 nm. Such concentrated polymer brushes can modify the surface of a substrate, imparting characteristics such as low friction, suppression of protein adsorption, size exclusion properties, hydrophilicity, and water repellency (Patent Documents 1 and 2).

[0004] Also, in order to hydrophilize the surface of a substrate, a method has been proposed in which the substrate is coated with a polymer formed by polymerizing a monomer having a hydrophilic group or a hydrophilic structure, such as a polyethylene glycol chain, a sulfobetaine group, a carboxybetaine group, or a phosphorylcholine group, thereby introducing a hydrophilic group or the like onto the surface of the substrate (Patent Documents 3 to 5). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2008-133434 A [Patent Document 2] JP 2010-261001 A [Patent Document 3] JP 2006-002147 A [Patent Document 4] JP 2003-213541 A [Patent Document 5] JP 2004-068174 A Summary of the Invention [Problem to be solved by the invention]

[0006] Monomers having a hydrophilic group such as a betaine group used in the methods proposed in Patent Documents 3 to 5 are soluble in water but are poorly soluble in organic solvents commonly used as polymerization solvents, so there are limitations to the polymerization method. In addition, the polymer layer formed from a polymer that is a polymer of the above-mentioned monomers having a hydrophilic group does not have very good durability such as water resistance.

[0007] The present invention has been made in consideration of the problems of the prior art, and an object of the present invention is to provide a method for producing a hydrophilic film that can easily form a hydrophilic film having a sufficient thickness and excellent hydrophilicity on the surface of a substrate.Another object of the present invention is to provide a surface-hydrophilized substrate having a hydrophilic film having a sufficient thickness and excellent hydrophilicity provided on the surface of a substrate. [Means for solving the problem]

[0008] That is, according to the present invention, there is provided a method for producing a hydrophilic film as described below. [1] A method for producing a hydrophilic film comprising the steps of: polymerizing at least one monomer selected from the group consisting of dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, and dimethylaminopropyl methacrylamide to form a polymer (i) bonded to the surface of a substrate in a structure represented by the following general formula (1); and providing a precursor polymer layer containing the polymer (i) on the surface of the substrate; and reacting at least one reactant selected from the group consisting of sodium chloroacetate, sodium 2-chloropropionate, 1,3-propane sultone, 1,4-butane sultone, ethylene methyl phosphate, and ethylene ethyl phosphate with the polymer (i) to form a polymer (ii) having a zwitterionic group; and providing a hydrophilic film containing the polymer (ii) on the surface of the substrate, wherein the number average molecular weight of the polymer (i) is 500,000 to 5,000,000 and the molecular weight distribution (weight average molecular weight / number average molecular weight) is 1.1 to 2.0, the thickness of the precursor polymer layer is 500 to 3,000 nm, and the amount of the polymer (i) bonded to the surface of the substrate is 1 nm or less on the surface of the substrate. 2 A method for producing a hydrophilic film having 0.2 molecular chains or more per unit area.

[0009] TIFF0007605435000001.tif27170 (In the general formula (1), A represents O or NH; R1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group, or an acyl group; R2 represents a methyl group, an ethyl group, or an acyl group; "Polymer(i)" represents polymer (i); and "*" represents the bonding position with the substrate surface.)

[0010] [2] The method for producing a hydrophilic film according to the above [1], wherein the polymer (i) is formed by surface radical polymerization initiated by a polymerization initiating group represented by the following general formula (2):

[0011] TIFF0007605435000002.tif27170 (In the general formula (2), A represents O or NH, R1 represents a hydrogen atom, an alkyl group, an acyl group, or an aryl group, R2 represents an alkyl group or an aryl group, X represents a chlorine atom, a bromine atom, or an iodine atom, and "*" represents the bonding position with the substrate surface.)

[0012] [3] The method for producing a hydrophilic film according to [2], wherein the polymerization initiating group represented by the general formula (2) is at least one of a 2-bromo-2-methylpropanoyloxy group and a 2-bromo-2-methylpropanoylamino group. [4] The method for producing a hydrophilic film according to any one of [1] to [3] above, wherein the polymer (i) is formed by surface-initiated living radical polymerization of the monomer under a pressure condition of 10 to 500 MPa.

[0013] The present invention also provides the following surface-hydrophilized substrate. [5] A hydrophilic film comprising a substrate and a polymer (ii) provided on a surface of the substrate, the substrate surface and the polymer (ii) being bonded to each other through a structure represented by the following general formula (3), the polymer (ii) containing 50 mass % or more of repeating units of at least one monomer selected from the following hydrophilic monomer group, the hydrophilic film having a thickness of 600 to 4,000 nm, and the amount of the polymer (ii) bonded to the substrate surface being within 1 nm of the substrate surface. 2 A hydrophilic surface substrate having 0.2 molecular chains or more per unit area.

[0014] [Hydrophilic monomer group]: 2-[[2-(methacryloyloxy)ethyl]dimethyl Ammonio ]acetate, 2 -[[2-(methacryloyloxy)ethyl]dimethyl Ammonio ]propionate, 3-[[2-(methacryloyloxy)ethyl]dimethyl Ammonio ]propane-1-sulfonate, 4 -[[2-(methacryloyloxy)ethyl]dimethyl Ammonio ]butane-1-sulfonate, 2-[2-(methacryloyloxy)ethyldimethyl Ammonio ]ethyl methyl phosphate, 2-[2-(methacryloyloxy)ethyl dimethyl Ammonio ]ethyl ethyl phosphate, 2-[[2-(methacryloyloxy)ethyl]diethyl Ammonio ]acetate, 2-[[2-(methacryloyloxy)ethyl]diethyl Ammonio ]propionate, 3-[[2-(methacryloyloxy)ethyl]diethyl Ammonio ]propane-1-sulfonate, 4 -[[2-(methacryloyloxy)ethyl]diethyl Ammonio ]butane-1-sulfonate, 2-[2-(methacryloyloxy)ethyl diethyl Ammonio ]ethyl methyl phosphate, 2-[2-(methacryloyloxy)ethyl diethyl Ammonio ]ethyl ethyl phosphate, 2 -[[3-(methacryloylamino) Propyl ]Dimethyl Ammonio ]acetate, 2 -[[3-(methacryloylamino) Propyl ]Dimethyl Ammonio ]propionate, 3-[(3-methacryloylaminopropyl)dimethyl Ammonio ]propane-1-sulfonate, 4 -[(3-Methacryloylaminopropyl)dimethyl Ammonio ]butane-1-sulfonate, 2 -[[3-(methacryloylamino) Propyl ]Dimethyl Ammonio ]ethyl methyl phosphate, 2 -[[3-(methacryloylamino) Propyl ]Dimethyl Ammonio ]Ethyl ethyl phosphate

[0015] TIFF0007605435000003.tif28170 (In the general formula (3), A represents O or NH, R1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group, or an acyl group, R2 represents a methyl group, an ethyl group, or an acyl group, "Polymer(ii)" represents polymer (ii), and "*" represents the bonding position with the substrate surface.) Effect of the Invention

[0016] According to the present invention, it is possible to provide a method for producing a hydrophilic film that can easily form a hydrophilic film having a sufficient thickness and excellent hydrophilicity on the surface of a substrate. Also, according to the present invention, it is possible to provide a surface-hydrophilized substrate in which a hydrophilic film having a sufficient thickness and excellent hydrophilicity is provided on the surface of a substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] <Method of manufacturing hydrophilic film> Hereinafter, the embodiments of the present invention will be described, but the present invention is not limited to the following embodiments. The method for producing a hydrophilic film of the present invention includes a step (step (1)) of polymerizing a specific monomer to form a polymer (i) bonded to the surface of a substrate in a structure represented by the following general formula (1), and providing a precursor polymer layer containing the polymer (i) on the surface of the substrate, and a step (step (2)) of reacting the polymer (i) with a specific reactant to form a polymer (ii) having a zwitterionic group, and providing a hydrophilic film containing the polymer (ii) on the surface of the substrate. The number average molecular weight of the polymer (i) is 500,000 to 5,000,000, and the molecular weight distribution (weight average molecular weight / number average molecular weight) is 1.1 to 2.0. The thickness of the precursor polymer layer is 500 to 3,000 nm. The amount of the polymer (i) bonded to the surface of the substrate is 1 nm 2 The number of molecular chains per unit area is 0.2 or more. The method for producing a hydrophilic film of the present invention (hereinafter, also simply referred to as "the production method (of the present invention)") will be described in detail below.

[0018] TIFF0007605435000004.tif27170 (In the general formula (1), A represents O or NH; R1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group, or an acyl group; R2 represents a methyl group, an ethyl group, or an acyl group; "Polymer(i)" represents polymer (i); and "*" represents the bonding position with the substrate surface.)

[0019] (Process (1)) In step (1), a polymer (i) bonded to the surface of the substrate in a structure represented by general formula (1) is formed, and a precursor polymer layer containing the polymer (i) is provided on the surface of the substrate. The substrate may be any of natural products, artificial products, inorganic materials, and organic materials. Examples of the shape of the substrate include lumps, fine particles, powders, sheets, films, pellets, and plates. Specific examples include mechanical parts such as metals, metal oxides, metal nitrides, metal carbides, ceramics, wood, silicon compounds, thermoplastic resins, thermosetting resins, cellulose, and glass, as well as films, fibers, and sheets. More specific examples of the substrate include silicon substrates; glass substrates; metal plates such as stainless steel; ceramic plates formed of ceramics such as alumina, silicon carbide, and boron nitride; ITO films; plate-like or film-like substrates such as plastic plates and plastic films; fibrous substrates such as glass fibers and carbon fibers; and the like. The substrate may also be a filler-like material such as pigments, silica, and magnetic powder.

[0020] Polymer (i) is bonded to the surface of the substrate via a structure represented by general formula (1). Examples of the structure represented by general formula (1) (the structure of the portion excluding "Polymer (i)") include an ethylenecarbonyloxy group, a 1-propylenecarbonyloxy group, an acetylmethylenecarbonyloxy group, a 2-propylenecarbonyloxy group, a 2-butylenecarbonyloxy group, a 1-phenyl-1-ethylenecarbonyloxy group, a 1-phenyl-1-propylenecarbonyloxy group, an ethylenecarbonylamino group, a 1-propylenecarbonylamino group, an acetylmethylenecarbonylamino group, a 2-propylenecarbonylamino group, a 2-butylenecarbonylamino group, a 1-phenyl-1-ethylenecarbonylamino group, and a 1-phenyl-1-propylenecarbonylamino group. Among these, a 2-propylenecarbonyloxy group or a 2-propylenecarbonylamino group derived from 2-bromoisobutyric acid bromide or the like, which is a compound capable of introducing a polymerization initiating group with good initiation efficiency under mild living radical polymerization conditions, is preferred.

[0021] The polymer (i) is a methacrylate-based polymer or a methacrylamide-based polymer formed by polymerizing at least one monomer (amino group-containing monomer) selected from the group consisting of dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, and dimethylaminopropyl methacrylamide. That is, the polymer (i) is a methacrylate-based polymer or a methacrylamide-based polymer having a constitutional unit derived from at least one monomer selected from the group consisting of dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, and dimethylaminopropyl methacrylamide.

[0022] The polymer (i) is preferably substantially composed of only the constituent units derived from the amino group-containing monomer. The polymer (i) may further have constituent units derived from other methacrylate monomers or methacrylamide monomers, if necessary. Examples of other methacrylate monomers include aliphatic alkyl, alicyclic alkyl, aromatic, and ether group-containing methacrylates such as methyl, ethyl, propyl, butyl, isobutyl, t-butyl, hexyl, octyl, 2-ethylhexyl, decyl, isodecyl, dodecyl, stearyl, behenyl, cyclohexyl, t-butylcyclohexyl, trimethylcyclohexyl, tricyclodecyl, isobornyl, adamantyl, phenyl, benzyl, tetrahydrofurfuryl, and polyethylene glycol monomethyl ether. Examples of other methacrylamide monomers include methacrylamide, dimethyl methacrylamide, diethyl methacrylamide, and dibutyl methacrylamide.

[0023] In the polymer (i), the ratio of the constitutional unit derived from the amino group-containing monomer is preferably 50% by mass or more, more preferably 80% by mass or more, and most preferably 100% by mass. If the ratio of the constitutional unit derived from the amino group-containing monomer in the polymer (i) is less than 50% by mass, the hydrophilicity of the obtained hydrophilized film may be slightly decreased.

[0024] A polymer (i) bonded to the surface of a substrate in a structure represented by general formula (1) can be formed by surface radical polymerization, preferably surface living radical polymerization, initiated by a polymerization initiating group represented by the following general formula (2):

[0025] TIFF0007605435000005.tif27170 (In the general formula (2), A represents O or NH, R1 represents a hydrogen atom, an alkyl group, an acyl group, or an aryl group, R2 represents an alkyl group or an aryl group, X represents a chlorine atom, a bromine atom, or an iodine atom, and "*" represents the bonding position with the substrate surface.)

[0026] Examples of the polymerization initiating group represented by the general formula (2) include a 2-chloropropanoyloxy group, a 2-bromopropanoyloxy group, a 3-iodopropanoyloxy group, a 2-chloropropanoylamino group, a 2-bromopropanoylamino group, a 2-iodopropanoylamino group, a 2-chloro-2-methylpropanoyloxy group, a 2-bromo-2-methylpropanoyloxy group, a 2-iodo-2-methylpropanoyloxy group, a 2-chloro-2-methylpropanoylamino group, group, 2-bromo-2-methylpropanoylamino group, 2-iodo-2-methyl-propanoylamino group, 2-chlorobutanoyloxy group, 2-bromobutanoyloxy group, 3-iodobutanoyloxy group, 2-chlorobutanolamino group, 2-bromobutanoylamino group, 2-iodobutanoylamino group, chlorophenylacetyloyloxy group, bromophenylacetyloyloxy group, iodophenylacetyloyloxy group, chlorophenylacetyloyl Amino group, bromophenylacetyloylamino group, iodophenylacetyloylamino group, chloromethylphenylacetyloyloxy group, bromomethylphenylacetyloyloxy group, iodomethylphenylacetyloyloxy group, chloromethylphenylacetyloylamino group, bromomethylphenylacetyloylamino group, iodomethylphenylacetyloylamino group, chlorodiphenylacetyloyloxy group, bromodiphenylacetyloyloxy Examples of the aryl group include an iododiphenylacetyloyloxy group, a chlorodiphenylacetyloylamino group, a bromodiphenylacetyloylamino group, an iododiphenylacetyloylamino group, a chloroacetoxyacetyloyloxy group, a bromoacetoxyacetyloyloxy group, an iodoacetoxyacetyloylamino group, a chloroacetoxyacetyloyloxy group, a bromoacetoxyacetyloylamino group, an iodoacetoxyacetyloylamino group, etc. From the viewpoint of polymerizability and availability, etc., a 2-chloropropanoyloxy group, a 2-chloropropanoylamino group, a 2-bromo-2-methylpropanoyloxy group, and a 2-bromo-2-methylpropanoylamino group are preferred, and at least one of a 2-bromo-2-methylpropanoyloxy group and a 2-bromo-2-methylpropanoylamino group is particularly preferred.

[0027] The polymerization initiator group can be introduced onto the surface of the substrate by dehydration condensation reaction between a compound having a polymerization initiator group and a silane coupling group such as a trimethoxysilyl group or a triethylsilyl group and a hydroxyl group on the surface of the substrate, or by dehydration condensation reaction between a compound having a polymerization initiator group and a silanol group previously applied to the surface of the substrate using a silane monomer such as tetraethoxysilane. The substrate may also be coated with a polymer having a polymerization initiator group.

[0028] At least one monomer selected from the group consisting of dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, and dimethylaminopropyl methacrylamide is polymerized by surface radical polymerization, preferably surface-initiated living radical polymerization, initiated by a polymerization initiating group represented by general formula (2).This forms a polymer (i) having one end bonded to the substrate via a predetermined structure, and a precursor polymer layer containing the formed polymer (i) can be provided on the surface of the substrate.

[0029] Among surface-initiated living radical polymerizations, atom transfer radical polymerization (ATRP) is preferred because it is easy to introduce an initiator group. In the ATRP method, an organic halide is used as an initiator group, and a complex of a metal ion such as a copper ion or a ruthenium ion with a polyamine as a ligand is used as a catalyst. This catalyst extracts a halogen atom as a radical from the initiator group, changes the valence of the metal ion, and stabilizes the structure of the metal halide salt. The residue of the organic halide generated by extracting the halogen atom becomes an organic radical. Polymerization proceeds by adding a monomer to this organic radical. However, since the generated organic radical is unstable, a halogen atom is extracted as a radical from the catalyst that has become a metal halide salt, and the resulting organic halide is stabilized. This prevents termination reactions such as coupling of the organic radical. The valence of the catalyst of the metal ion from which the halogen atom has been extracted returns to the original value. In other words, the ATRP method is a polymerization method that utilizes an oxidation-reduction reaction, and by repeating the oxidation-reduction reaction, a monomer reacts with the organic halide as an initiator group and polymerizes to grow. In this polymerization reaction, the radical concentration is low, so the monomers grow one to several molecules at a time, and a polymer with a relatively uniform molecular weight is produced. By applying this type of ATRP method to surface-initiated living radical polymerization, it is possible to form concentrated polymer brushes.

[0030] As the living radical polymerization method, the above-mentioned ATRP method using a conventionally known metal complex is suitable. As the metal complex, a metal complex having an element of Groups 7 to 11 of the periodic table as a central metal can be used. Specifically, metal complexes containing monovalent copper, divalent copper, divalent ruthenium, divalent iron, and divalent nickel can be mentioned. Among them, metal complexes containing monovalent copper and divalent copper, which are inexpensive and easily available, are preferred, and cuprous chloride, cupric chloride, cuprous bromide, cupric bromide, cuprous iodide, and cupric iodide are more preferred.

[0031] When a copper metal complex is used as a polymerization catalyst, a polyamine is used as a ligand for forming the complex. Examples of polyamines used as ligands include 2,2-bipyridine, dinonyl bipyridine, phenanthroline, tridimethylaminoethylamine, pentamethyldiethylenetriamine, tris[2-(dimethylamino)ethyl]amine, tris(2-picolyl)amine, and N,N,N',N'-tetrakis(2-pyridylmethyl)ethylenediamine. The amount of the metal complex (polymerization catalyst) relative to the methacrylate monomer is preferably 0.001 to 0.1% by mass.

[0032] In order to prevent the deactivation of the catalyst during polymerization, a reducing agent may be used. Examples of the reducing agent include tin dilaurate and ascorbic acid. In addition, an azo-based polymerization initiator such as azobisisobutyronitrile may be added to promote the activation of the polymerization. The ATRP method may be bulk polymerization or solution polymerization using an organic solvent or the like.

[0033] The ATRP method may be bulk polymerization or solution polymerization using an organic solvent or the like. Examples of the organic solvent that can be used include hydrocarbon solvents, ester solvents, glycol solvents, ether solvents, amide solvents, alcohol solvents, sulfoxide solvents, urea solvents, and ionic liquids. By using a solvent with high polarity, the polymerization rate can be increased and the film thickness can be increased, which is preferable. Specifically, it is preferable to use an ionic liquid, and it is more preferable to use an ionic liquid such as a quaternary ammonium salt, an imidazolium salt, a pyridinium salt, a quaternary phosphonium salt, or a guanidinium salt.

[0034] It is also preferable to polymerize a methacrylate monomer in the presence of a general-purpose organic compound that does not use heavy metals. As a method for polymerizing in the presence of an organic compound, a reversible catalyst-mediated polymerization method (RCMP method) can be mentioned. Specifically, it is preferable to polymerize by immersing a substrate in a polymerization system containing at least one salt selected from the group consisting of quaternary ammonium halide salts, quaternary phosphonium halide salts, and alkali metal halide salts. This allows polymerization using commercially available inexpensive organic materials and inorganic salts. In addition, since there is no need to remove metals, the burden on the environment can be reduced and the process can be simplified.

[0035] Examples of the quaternary ammonium halide salt include benzyltrimethylammonium chloride, tetrabutylammonium bromide, tetrabutylammonium iodide, tetraoctylammonium iodide, nonylpyridinium chloride, and choline chloride. Examples of the quaternary phosphonium halide salt include tetraphenylphosphonium chloride, methyltributylphosphonium bromide, and tetrabutylphosphonium iodide. Examples of the alkali metal halide salt include lithium bromide, potassium iodide, and sodium iodide.

[0036] As the salt, it is preferable to use an iodide salt. By using an iodide salt, living radical polymerization proceeds, and a precursor polymer with a narrower molecular weight distribution can be formed. In addition, it is preferable to use a salt that can be dissolved in a polymerization solution, such as a quaternary ammonium iodide salt, a quaternary phosphonium iodide salt, and an alkali metal iodide salt, and it is more preferable to use a quaternary ammonium iodide salt. Examples of the quaternary ammonium iodide salt include benzyltetrabutylammonium iodide, tetrabutylammonium iodide, tetraoctylammonium iodide, dedosyltrimethylammonium iodide, octadecyltrimethylammonium iodide, and trioctadecylmethylammonium iodide. These salts are used as catalysts and are different from the organic salts described above. In addition, since these salts are used as catalysts, the amount of addition is extremely small compared to the organic salts described above.

[0037] From the viewpoint of increasing the activity and forming a more concentrated and high molecular weight polymer (i), the amount of the salt relative to the polymerization initiating group is preferably at least an equimolar amount, more preferably at least 10 times the molar amount, and may be at least 100 times the molar amount.

[0038] The polymerization reaction is usually carried out under normal pressure conditions. However, in order to stably form a high molecular weight polymer (i), it is preferable to extend the polymerization time while suppressing the termination reaction derived from the radical polymerization. For this reason, it is preferable to form the polymer (i) by subjecting the monomer to surface-initiated living radical polymerization under a pressure (external pressure) condition of preferably 10 to 500 MPa, more preferably 50 to 400 MPa. However, it is somewhat difficult to prepare a container or device that can withstand a pressure of more than 500 MPa, and it cannot be said to be very practical.

[0039] As the polymerization vessel, it is preferable to use a vessel that can be sealed and can withstand high pressure. In addition, since pressure needs to be transmitted to the inside of the vessel, it is preferable to use a vessel having a part that deforms under pressure, such as a soft part or an expandable part made of plastic. Specifically, various vessels such as polyethylene bottles, PET bottles, retort pouches, and blister containers can be used. In addition, a vessel made of a material that is not easily deformed at the temperature during polymerization and has heat resistance is preferable. Furthermore, a vessel made of a material that is not easily damaged by the solvent for polymerization and has properties such as chemical resistance and solvent resistance is preferable. Examples of materials that constitute the polymerization vessel include polyolefin resins, fluorine resins, polyester resins, polyamide resins, and engineering plastics. In addition, it is preferable to prevent gas from entering the polymerization vessel as much as possible during polymerization. For example, it is preferable to charge the polymerization solution to 90% or more of the volume of the polymerization vessel.

[0040] The number average molecular weight (Mn) of the polymer (i) is 500,000 to 5 million, preferably 800,000 to 4 million, more preferably 1 million to 3 million. If the Mn of the polymer (i) is less than 500,000, the thickness of the precursor polymer layer and the hydrophilized film formed is insufficient. On the other hand, it is difficult to polymerize the polymer (i) having an Mn of more than 5 million, and the termination reaction in the side reaction progresses a lot, and the molecular weight distribution (PDI) may become excessively large. In this specification, the Mn and Mw of the polymer (i) are values ​​calculated as polymethyl methacrylate measured by gel permeation chromatography (GC).

[0041] The molecular weight distribution of the polymer (i) (PDI=weight average molecular weight (Mw) / number average molecular weight (Mn)) is 1.1 to 2.0, preferably 1.15 to 1.8, and more preferably 1.2 to 1.5. It is practically difficult to form a polymer (i) having a PDI of less than 1.1. On the other hand, if the PDI exceeds 2.0, the performance of the concentrated polymer brush may not be fully exhibited, and the smoothness of the precursor polymer layer and the hydrophilized film may be slightly reduced. By forming a polymer (i) having a relatively narrow molecular weight distribution, the growing ends of the polymer (i) are relatively uniform, and a precursor polymer layer and a hydrophilized film having a relatively flat surface can be provided. In addition, by setting the Mn and PDI of the polymer (i) within the above ranges, the generation density of the polymer (i) relative to the substrate is high, and a precursor polymer layer and a hydrophilized film that are concentrated polymer brushes of sufficient thickness can be obtained.

[0042] The Mn and Mw of the polymer (i) can be measured by removing the polymer (i) from the substrate. Methods for removing the polymer (i) from the substrate include a method of treating with hydrofluoric acid or concentrated alkali, a method of hydrolysis, and the like. In addition, a methacrylate monomer is polymerized in the presence of a compound having a polymerization initiator group (a so-called free initiator compound) to form a free polymer that is not bonded to the surface of the substrate. The Mn and Mw of the polymer stretched from the free initiator compound can be estimated as the Mn and Mw of the polymer (i).

[0043] The thickness of the precursor polymer layer provided on the substrate surface is 500 to 3,000 nm, preferably 600 to 2,000 nm, and more preferably 700 to 1,500 nm. If the thickness of the precursor polymer layer is less than 500 nm, it is difficult to exhibit the performance as a hydrophilic film for hydrophilizing the substrate surface, and durability such as abrasion resistance is insufficient. On the other hand, in order to form a precursor polymer layer with a thickness of more than 3,000 nm, it is necessary to make the molecular weight of the polymer (i) very large, so that the polymerization time becomes excessively long and the molecular weight distribution of the polymer (i) may become too wide.

[0044] The amount of polymer (i) bound to the surface of the substrate is 2 The molecular chains per nanometer of the surface of the substrate are 0.2 or more, preferably 0.2 to 1 molecular chain, and more preferably 0.2 to 0.7 molecular chains. 2 The amount of polymer (i) bonded per unit is the graft density σ (particles / nm 2 ) The polymer (i) is stretched from the polymerization initiation group on the surface of the substrate as the origin in a direction perpendicular to the substrate to form a precursor polymer layer. By setting the graft density σ of the polymer (i) within the above range, it is possible to exhibit properties such as high elasticity, ultra-low friction, and size exclusion effect. When the graft density σ is 0.2 strands / nm 2 If the number is less than 1 / nm, the above characteristics are not fully exhibited. 2 It is generally difficult to achieve a graft density σ greater than 100 nm.

[0045] Graft density σ (particles / nm 2 ) can be calculated by the following formula (A). The thickness of the precursor polymer layer can be measured by a conventionally known method using, for example, an ellipsometer, an electron microscope, an atomic force microscope, or the like. The density of the polymer (i) can be a value described in a conventionally known document or a value measured by a method described in JIS K 7112:1999, or the like. σ = dLNAMn (A) d: density of polymer (polymer (i)) L: Thickness of the polymer layer (precursor polymer layer) NA: Avogadro's number Mn: number average molecular weight of polymer (polymer (i))

[0046] (Process (2)) In step (2), the polymer (i) formed in step (1) is reacted with a specific reactant to form a polymer (ii) having zwitterionic groups, thereby forming a hydrophilic film containing the polymer (ii) on the surface of the substrate.

[0047] As the specific reactant to be reacted with the polymer (i), at least one selected from the group consisting of sodium chloroacetate, sodium 2-chloropropionate, 1,3-propane sultone, 1,4-butane sultone, ethylene methyl phosphate, and ethylene ethyl phosphate is used. To react these reactants with the polymer (i), for example, a substrate (precursor substrate) having a precursor polymer layer containing the polymer (i) on its surface is immersed in a polar solvent such as water, a lower alcohol, an amide solvent, or a sulfoxide solvent, or a mixed solvent thereof, and the reactant is added. The reaction temperature may be room temperature (25°C) or may be heated to 100°C or lower. As a result, the amino group of the polymer (i) reacts with the reactant, and the polymer (i) is converted into a polymer (ii) having zwitterionic groups in the molecule that exhibit anionic and cationic properties, and a hydrophilic film containing the polymer (ii) is disposed on the surface of the substrate.

[0048] When sodium chloroacetate or sodium 2-chloropropionate is reacted with polymer (i), sodium chloride is generated, and a carboxybetaine structure can be formed. When 1,3-propane sultone or 1,4-butane sultone is reacted with polymer (i), these reactants undergo a ring-opening reaction to form a sulfobetaine structure. When ethylene methyl phosphate or ethylene ethyl phosphate is reacted with polymer (i), these reactants undergo a ring-opening reaction to form a phosphate betaine structure. Regardless of which reactant is used, a hydrophilic polymer (ii) is formed in which a zwitterionic group having an anion and a cation in the molecule is introduced, and a hydrophilized film containing polymer (ii) can be obtained.

[0049] <Surface hydrophilic base material> By the above-mentioned manufacturing method, it is possible to obtain a surface-hydrophilized substrate having a hydrophilized film disposed on the surface of the substrate. That is, the surface-hydrophilized substrate of the present invention comprises a substrate and a hydrophilized film containing polymer (ii) disposed on the surface of the substrate. The surface of the substrate and polymer (ii) are bonded to each other through a structure represented by the following general formula (3). Polymer (ii) contains 50 mass % or more of repeating units of at least one monomer selected from the following "hydrophilic monomer group". The thickness of the hydrophilized film is 600 to 4,000 nm, and the amount of polymer (ii) bonded to the surface of the substrate is 1 nm thick. 2 The molecular chain per unit area is 0.2 or more. The surface-hydrophilized substrate of the present invention will be described in detail below.

[0050] [Hydrophilic monomer group]: 2-[[2-(methacryloyloxy)ethyl]dimethyl Ammonio ]acetate, 2 -[[2-(methacryloyloxy)ethyl]dimethyl Ammonio ]propionate, 3-[[2-(methacryloyloxy)ethyl]dimethyl Ammonio ]propane-1-sulfonate, 4 -[[2-(methacryloyloxy)ethyl]dimethyl Ammonio ]butane-1-sulfonate, 2-[2-(methacryloyloxy)ethyldimethyl Ammonio ]ethyl methyl phosphate, 2-[2-(methacryloyloxy)ethyl dimethyl Ammonio ]ethyl ethyl phosphate, 2-[[2-(methacryloyloxy)ethyl]diethyl Ammonio ]acetate, 2 -[[2-(methacryloyloxy)ethyl]diethyl Ammonio ]propionate, 3-[[2-(methacryloyloxy)ethyl]diethyl Ammonio ]propane-1-sulfonate, 4 -[[2-(methacryloyloxy)ethyl]diethyl Ammonio ]butane-1-sulfonate, 2-[2-(methacryloyloxy)ethyl diethyl Ammonio ]ethyl methyl phosphate, 2-[2-(methacryloyloxy)ethyl diethyl Ammonio ]ethyl ethyl phosphate, 2 -[[3-(methacryloylamino) Propyl ]Dimethyl Ammonio ]acetate, 2 -[[3-(methacryloylamino) Propyl ]Dimethyl Ammonio ]propionate, 3-[(3-methacryloylaminopropyl)dimethyl Ammonio ]propane-1-sulfonate, 4 -[(3-Methacryloylaminopropyl)dimethyl Ammonio ]butane-1-sulfonate, 2 -[[3-(methacryloylamino) Propyl ]Dimethyl Ammonio ]ethyl methyl phosphate, 2 -[[3-(methacryloylamino) Propyl ]Dimethyl Ammonio ]Ethyl ethyl phosphate

[0051] TIFF0007605435000006.tif28170 (In the general formula (3), A represents O or NH, R1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group, or an acyl group, R2 represents a methyl group, an ethyl group, or an acyl group, "Polymer(ii)" represents polymer (ii), and "*" represents the bonding position with the substrate surface.)

[0052] The hydrophilic film including the polymer (ii) provided on the surface of the substrate, preferably substantially composed of the polymer (ii), can be formed by reacting a specific reactant with the polymer (i) constituting the precursor polymer layer of the precursor substrate, as described above. That is, by reacting the specific reactant with the polymer (i), the polymer (i) is converted into a polymer (ii) including a repeating unit of at least one monomer (hydrophilic monomer) selected from the above hydrophilic monomer group, and the hydrophilic film including the polymer (ii) is provided on the surface of the substrate.

[0053] In the polymer (ii), the ratio of the constitutional units derived from the hydrophilic monomer is preferably 50% by mass or more, more preferably 80% by mass or more, and most preferably 100% by mass. If the ratio of the constitutional units derived from the hydrophilic monomer in the polymer (ii) is less than 50% by mass, the hydrophilicity of the formed hydrophilized film may decrease.

[0054] A common method for providing a hydrophilic film on the surface of a substrate is to coat the surface of the substrate with a polymer having a structural unit derived from a betaine monomer. However, the hydrophilic film formed by coating a conventional polymer having a structural unit derived from a betaine monomer is not very water resistant, and is often difficult to crosslink, resulting in reduced durability. In contrast, the hydrophilic film constituting the surface-hydrophilized substrate is formed of a polymer containing many structural units derived from a betaine monomer, but one end of the film is bonded to the substrate, so it has excellent durability such as abrasion resistance. Furthermore, the hydrophilic film has a sufficient thickness and is more durable and hydrophilic than a general coating film.

[0055] When the polymer (i) is reacted with a reactant, the amino group in the polymer (i) is converted into a betaine structure, so that the thickness of the precursor polymer layer increases to form a hydrophilic film. Therefore, the thickness of the hydrophilic film is 600 to 4,000 nm, preferably 700 to 3,000 nm. If the thickness of the hydrophilic film is less than 600 nm, the durability and hydrophilicity are insufficient. On the other hand, in order to form a hydrophilic film with a thickness of more than 4,000 nm, the molecular weight of the polymer (i) needs to be very large, so that the polymerization time becomes excessively long and the molecular weight distribution of the polymer (i) may become too wide, which is not very practical.

[0056] The amount of polymer (ii) bound to the surface of the substrate is 2 The molecular chains per nanometer of the surface of the substrate are 0.2 or more, preferably 0.2 to 1 molecular chain, and more preferably 0.2 to 0.7 molecular chains. 2The amount of polymer (ii) bonded per unit area is determined by the graft density σ (particles / nm 2 ) The graft density σ of the polymer (ii) does not vary significantly from the graft density σ of the precursor polymer (i). Therefore, by setting the graft density σ of the polymer (ii) within the above range, it is possible to exhibit properties such as high elasticity, ultra-low friction, and size exclusion effect.

[0057] The surface-hydrophilized substrate of the present invention has a sufficient thickness of the hydrophilized film disposed on the surface, and the polymer (ii) constituting the hydrophilized film has a high molecular weight and is densely formed, so that the durability and hydrophilicity of the surface are good. Since the surface-hydrophilized substrate of the present invention has a hydrophilized film with excellent durability, it is suitable for use under harsh conditions such as outdoor use and sliding use. Furthermore, since the surface-hydrophilized substrate of the present invention has excellent hydrophilicity and has a hydrophilized film that can swell with a solvent such as water, it is expected to exhibit performance such as anti-fogging properties, contamination resistance, size exclusion properties, and extremely low friction. The surface-hydrophilized substrate of the present invention is suitable as an article used in various fields such as medical materials, electronic materials, display materials, semiconductor materials, machine parts, sliding members, and battery materials. EXAMPLES

[0058] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, "parts" and "%" are by mass unless otherwise specified.

[0059] <Production of precursor substrate> (Production Example 1) A silicon substrate measuring 3 cm x 7.5 cm was prepared. The surface of the silicon substrate was ultrasonically cleaned with isopropyl alcohol (IPA), and then irradiated with UV ozone using a tip cleaner (manufactured by Bioforce Nano Science Co., Ltd.) to form hydroxyl groups on the surface of the silicon substrate, activating it. The activated silicon substrate was immersed for 12 hours in a container containing 100 parts of ethanol, 10 parts of 28% aqueous ammonia, and 1 part of 2-bromo-2-methylpropionyloxypropyltrimethoxysilane (BPM). The removed silicon substrate was washed with ethanol and then dried at 80°C for 10 minutes to obtain a silicon substrate having a polymerization initiator group on its surface (polymerization initiator group-imparted substrate). The contact angle (pure water) of the surface of the obtained polymerization initiator group-imparted substrate was 60°.

[0060] In a glass sample bottle, the inside of which was replaced with nitrogen gas, 0.0056 parts of copper bromide (II), 0.0681 parts of copper bromide (I), 0.17 parts of 2,2'-bipyridine (byp), 47.2 parts of dimethylaminoethyl methacrylate (DMAEMA), 47.1 parts of ethanol, and 0.2 parts of a 0.1% ethanol solution of ethyl bromoisobutyrate (EBIB, a free initiator compound) were added and stirred to obtain a brown polymerization solution. The polymerization solution and the polymerization initiator group-imparting substrate were placed in a polyethylene container with a screw cap and sealed. The container was placed in an aluminum laminate bag, and the polymerization solution was filled, and then the container was heat-sealed while removing the gas. The aluminum laminate bag was placed in a high-pressure device (trade name "PV-400", manufactured by Shin Corporation) containing water as a pressurizing medium, and polymerized at 40°C and 400 MPa for 4 hours to form a polymer (i).

[0061] After cooling, a portion of the polymerization solution in the vessel was sampled, and the number average molecular weight (Mn) of the formed polymer (i) was measured in terms of polymethyl methacrylate (PMMA) by gel permeation chromatography (GPC) using 1 mmol / L lithium chloride (LiCl) / dimethylformamide (DMF) as the developing solvent, and the molecular weight distribution (PDI=Mw / Mn) was calculated. The Mn of the formed polymer (i) was 2.55 million, and the PDI was 1.33.

[0062] The contents removed from the container were thoroughly washed with methanol and then dried at 80°C using a blower dryer to obtain a precursor substrate-1 in which a precursor polymer layer exhibiting rainbow interference was provided on the surface of a silicon substrate. The thickness of the precursor polymer layer was measured using a film thickness meter (product name "F20-UV", Filmetrics, Inc.) and was found to be 1,080 nm. The graft density σ of polymer (i) calculated from the thickness of the precursor polymer layer and the density (1.2) of polyDMAEMA was 0.29 strands / nm 2 Analysis using a surface infrared spectrophotometer (surface IR) revealed that the ester bond (1,725 ​​cm ) characteristic of polyDMAEMA was observed. -1 ) and amino groups (1,150cm -1 ) absorption was confirmed.

[0063] (Production Examples 2 to 4) Precursor substrates-2 to -4, in which a precursor polymer layer was provided on the surface of a silicon substrate, were obtained in the same manner as in Production Example 1 described above, except that the types of monomers shown in Table 1 were used and polymerization was performed under the pressure and polymerization time shown in Table 1. The meanings of the abbreviations in Table 1 are as follows. ·DEAEMA: Diethylaminoethyl methacrylate DMPMAM: Dimethylpropylmethacrylamide

[0064] TIFF0007605435000007.tif83170

[0065] (Production Example 5) In a glass sample bottle, the inside of which was replaced with nitrogen gas, the polymerization initiator group-imparted substrate obtained in Production Example 1, 1.25 parts of tetrabutylammonium iodide (TBAI), 40 parts of DMAEMA, 40 parts of 3-methoxy-N,N-dimethylpropanamide (MDPA), and 0.001 parts of EBiB were added and stirred to obtain a pale yellow polymerization solution. Next, similar to the above-mentioned Production Example 1, the polymerization was carried out at 80°C and 400 MPa for 6 hours to form a polymer (i), and a precursor substrate-5 in which a precursor polymer layer was provided on the surface of a silicon substrate was obtained. The Mn of the polymer (i) was 1.74 million, and the PDI was 1.45. The thickness of the precursor polymer layer was 670 nm, and the graft density σ was 0.27 / nm 2 This Production Example 5 is an example in which polymer (i) was formed by a reversible catalyst-mediated polymerization method accompanied by halogen exchange (RCMP method), unlike the above-mentioned Production Examples 1 to 4 (atom transfer radical polymerization method (ATRP method)).

[0066] <Production of hydrophilic membrane (production of substrate with hydrophilic surface)> Example 1 In a glass sample tube, 12.2 parts of 1,3-propane sultone, 20 parts of acetonitrile, and 80 parts of water were added and dissolved. The precursor substrate-1 produced in Production Example 1 was immersed in the solution and reacted at 60°C for 12 hours to form a polymer (ii) having zwitterionic groups. After cooling, the contents were taken out and thoroughly washed with methanol and pure water, and then dried at 80°C using a blower dryer to obtain a surface-hydrophilized substrate in which a hydrophilized film composed of polymer (ii) was provided on the surface of the substrate. The surface IR of the hydrophilized film was measured, and a 1,030 cm IR derived from the sulfonyl group was obtained. -1 It was confirmed that the hydrophilic film had an absorption near the surface of the precursor polymer layer. The thickness of the formed hydrophilic film was 1,670 nm, and it was confirmed that the film thickness was greater than that of the precursor polymer layer. The contact angle (water) of the hydrophilic film surface measured using a contact angle meter was 8°, confirming that the film had sufficient hydrophilicity. The hydrophilic film constituting the obtained surface-hydrophilized substrate was poly[3-[[2-(methacryloyloxy)ethyl]dimethyl Ammonio This membrane was formed by densely grafting ]propane-1-sulfonate] onto the substrate surface.

[0067] Example 2 In a glass sample tube, 1.2 parts of sodium 2-chloroacetate and 100 parts of water were added and dissolved. The precursor substrate-2 produced in Production Example 2 was immersed and reacted at 60°C for 12 hours to form a polymer (ii) having zwitterionic groups. After cooling, the contents were taken out and thoroughly washed with pure water, and then dried at 80°C using a blower dryer to obtain a surface-hydrophilized substrate in which a hydrophilized film composed of polymer (ii) was provided on the surface of the substrate. The surface IR of the hydrophilized film was measured, and the 1,600 cm originating from the carboxylate group was obtained. -1 It was confirmed that the hydrophilic film formed had an absorption near the surface of the precursor polymer layer. The thickness of the hydrophilic film was 1,510 nm, and it was confirmed that the film thickness was greater than that of the precursor polymer layer. The contact angle (water) of the hydrophilic film surface was 9°, and it was confirmed that the hydrophilic film had sufficient hydrophilicity. The hydrophilic film constituting the obtained surface-hydrophilized substrate was poly[3-[[2-(methacryloyloxy)ethyl]diethyl Ammonio This membrane was formed by densely grafting ]propane-1-sulfonate] onto the substrate surface.

[0068] Example 3 In a glass sample tube, 1.2 parts of ethyl ethylene phosphate, 20 parts of acetonitrile, and 80 parts of water were added and dissolved. The precursor substrate-3 produced in Production Example 3 was immersed and reacted at 60°C for 12 hours to form a polymer (ii) having zwitterionic groups. After cooling, the contents were taken out and thoroughly washed with pure water, and then dried at 80°C using a blower dryer to obtain a surface-hydrophilized substrate in which a hydrophilized film composed of polymer (ii) was provided on the surface of the substrate. The surface IR of the hydrophilized film was measured, and a 1,050 cm IR derived from the phosphate group was obtained. -1 It was confirmed that the hydrophilic film formed had an absorption near the surface of the precursor polymer layer. The thickness of the hydrophilic film was 1,260 nm, and it was confirmed that the film thickness was greater than that of the precursor polymer layer. The contact angle (water) of the hydrophilic film surface was 10°, and it was confirmed that the hydrophilic film had sufficient hydrophilicity. The hydrophilic film constituting the obtained surface-hydrophilized substrate was a poly 2 -[[3-(methacryloylamino) Propyl ]Dimethyl Ammonio] This film is formed by densely grafting ethyl methyl phosphate onto the surface of the substrate.

[0069] (Examples 4 and 5) A polymer (ii) having zwitterionic groups was formed in the same manner as in Example 1 described above, except that the precursor substrate and reactant types shown in Table 2 were used, and a surface-hydrophilized substrate was obtained in which a hydrophilized film made of polymer (ii) was provided on the surface of the substrate. The hydrophilized film constituting the surface-hydrophilized substrate obtained in Example 4 was poly(3-[[2-(methacryloyloxy)ethyl]dimethyl Ammonio The hydrophilic membrane constituting the surface-hydrophilized substrate obtained in Example 4 is a membrane formed by densely grafting propane-1-sulfonate onto the substrate surface. 2 -[[2-(methacryloyloxy)ethyl]dimethyl Ammonio ] This film is formed by densely grafting propionate onto the substrate surface.

[0070] TIFF0007605435000008.tif82170

[0071] Comparative Example 1 The inside of a glass sample bottle was replaced with nitrogen gas, and 3-[[2-(methacryloyloxy)ethyl]dimethyl Ammonio] 28 parts of propane-1-sulfonate, 140 parts of methanol, 0.0028 parts of copper (II) bromide, 0.034 parts of copper (I) bromide, 0.086 parts of byp, and 0.98 parts of a 0.1% methanol solution of EBIB were added and stirred to obtain a polymerization solution. The polymerization solution and the polymerization initiator group-imparting substrate were placed in a polyethylene container with a screw cap and sealed. The container was placed in an aluminum laminate bag, and the polymerization solution was filled, and then the container was heat-sealed while removing the gas. The aluminum laminate bag was placed in a high-pressure device containing water as a pressure medium, and the polymer was formed by polymerization at 40°C and 400 MPa for 4 hours. After cooling, a portion of the polymerization solution in the container was sampled, and the polyethylene oxide-equivalent Mn of the formed polymer was measured by GPC using 50 mmol / L tris(hydroxymethyl)aminomethane hydrochloride buffer as the developing solvent, and the PDI was calculated. The Mn of the formed polymer was 320,000, and the PDI was 1.38. The contents removed from the container were thoroughly washed with pure water, and then dried at 80°C using a blower dryer to obtain a hydrophilic surface substrate in which a hydrophilic film was provided on the surface of a silicon substrate. The thickness of the hydrophilic film was 75 nm, and the graft density σ of the polymer was 0.17 / nm 2 It was.

[0072] Comparative Example 2 In a glass sample tube, 2-[[2-(methacryloyloxy)ethyl]dimethyl Ammonio] Acetate (CBMA) 32.3 parts and pure water 32.3 parts were added to prepare a CBMA aqueous solution. Meanwhile, 0.0042 parts of copper bromide (II), 0.051 parts of copper bromide (I), 0.13 parts of byp, and 1.58 parts of 0.1% aqueous solution of 2-hydroxyethyl 2-bromo-2-methylpropanoate (free initiator compound) were added to a glass sample bottle whose inside was replaced with nitrogen gas and stirred. Furthermore, a CBMA aqueous solution was added to obtain a polymerization solution. The polymerization solution and the polymerization initiator group-imparting substrate were placed in a polyethylene container with a screw cap and sealed. This container was placed in an aluminum laminate bag, and the polymerization solution was filled, and then heat-sealed while removing the gas. The aluminum laminate bag was placed in a high-pressure device containing water as a pressurizing medium, and polymerized at 40 ° C and 400 MPa for 4 hours to form a polymer. After cooling, a portion of the polymerization solution in the vessel was sampled, and the polyethylene oxide-equivalent Mn of the formed polymer was measured by GPC using 50 mmol / L tris(hydroxymethyl)aminomethane hydrochloride buffer as the developing solvent, and the PDI was calculated. However, since there was not a sufficient amount of polymer, it was not possible to measure and calculate Mn and PDI. The contents removed from the vessel were thoroughly washed with pure water, and then dried at 80°C using a blower dryer to obtain a surface-hydrophilized substrate in which a hydrophilized film was provided on the surface of a silicon substrate. The thickness of the hydrophilized film was 18 nm. [Industrial Applicability]

[0073] The hydrophilized film produced by the production method of the present invention is a superhydrophilic concentrated polymer brush, and can impart properties such as high resilience and hydrophilicity to the surface of the substrate. Furthermore, by swelling, properties such as extremely low friction, size exclusion properties, contamination resistance, and high adhesion prevention can be exhibited. Furthermore, since it is highly hydrophilic, properties such as anti-fogging, oil resistance, and contamination resistance can be imparted to the surface of the substrate, and it is useful as a material applied to parts such as automobiles, aircraft, electronic devices, home appliances, battery components, medical materials, and display materials. In addition, according to the production method of the present invention, a hydrophilic concentrated polymer brush can be easily produced by using inexpensive equipment and inexpensive materials, and therefore it is also suitable for mass production.

Claims

1. A process of polymerizing at least one monomer selected from the group consisting of dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, and dimethylaminopropyl methacrylamide to form a polymer (i) bonded to a surface of a substrate in a structure represented by the following general formula (1), and providing a precursor polymer layer containing the polymer (i) on the surface of the substrate; reacting the polymer (i) with at least one reactant selected from the group consisting of sodium chloroacetate, sodium 2-chloropropionate, 1,3-propane sultone, 1,4-butane sultone, ethylene methyl phosphate, and ethylene ethyl phosphate to form a polymer (ii) having a zwitterionic group, and providing a hydrophilized film containing the polymer (ii) on the surface of the substrate; The polymer (i) has a number average molecular weight of 500,000 to 5,000,000 and a molecular weight distribution (weight average molecular weight / number average molecular weight) of 1.1 to 2.0; The thickness of the precursor polymer layer is 500 to 3,000 nm; The amount of the polymer (i) bound to the surface of the substrate is within 1 nm 2 A method for producing a hydrophilic film having 0.2 molecular chains or more per unit area. (In the above general formula (1), A represents O or NH, and R 1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group, or an acyl group; R 2 indicates a methyl group, an ethyl group, or an acyl group, "Polymer (i)" indicates polymer (i), and "*" indicates the bonding position with the substrate surface.

2. The method for producing a hydrophilic film according to claim 1 , wherein the polymer (i) is formed by surface radical polymerization initiated by a polymerization initiating group represented by the following general formula (2): (In the general formula (2), A represents O or NH, and R 1 represents a hydrogen atom, an alkyl group, an acyl group, or an aryl group; R 2 represents an alkyl group or an aryl group, X represents a chlorine atom, a bromine atom, or an iodine atom, and "*" represents the bonding position with the substrate surface.

3. 3. The method for producing a hydrophilic film according to claim 2, wherein the polymerization initiating group represented by the general formula (2) is at least one of a 2-bromo-2-methylpropanoyloxy group and a 2-bromo-2-methylpropanoylamino group.

4. The method for producing a hydrophilized film according to any one of claims 1 to 3, wherein the polymer (i) is formed by surface-initiated living radical polymerization of the monomer under a pressure condition of 10 to 500 MPa.

5. A substrate and a hydrophilic film containing a polymer (ii) provided on a surface of the substrate, The surface of the substrate and the polymer (ii) are bonded to each other via a structure represented by the following general formula (3): The polymer (ii) contains a repeating unit of at least one monomer selected from the following hydrophilic monomer group: The thickness of the hydrophilic film is 600 to 4,000 nm; The amount of the polymer (ii) bound to the surface of the substrate is within 1 nm 2 The surface of the hydrophilized substrate has 0.2 molecular chains or more per unit area. [Hydrophilic monomer group]: 2-[[2-(methacryloyloxy)ethyl]dimethylammonio]acetate, 2-[[2-(methacryloyloxy)ethyl]dimethylammonio]propionate, 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonate, 4-[[2-(methacryloyloxy)ethyl]dimethylammonio]butane-1-sulfonate, 2-[2-(methacryloyloxy)ethyl 2-[2-(methacryloyloxy)ethyldimethylammonio]ethyl methyl phosphate, 2-[[2-(methacryloyloxy)ethyldimethylammonio]ethyl ethyl phosphate, 2-[[2-(methacryloyloxy)ethyl]diethylammonio]acetate, 2-[[2-(methacryloyloxy)ethyl]diethylammonio]propionate, 3-[[2-(methacryloyloxy)ethyl]diethylammonio]propane-1-sulfonate, 4-[ [2-(methacryloyloxy)ethyl]diethylammonio]butane-1-sulfonate, 2-[2-(methacryloyloxy)ethyldiethylammonio]ethylmethylphosphate, 2-[2-(methacryloyloxy)ethyldiethylammonio]ethylethylphosphate, 2-[[3-(methacryloylamino)propyl]dimethylammonio]acetate, 2-[[3-(methacryloylamino)propyl]dimethylammonio]propionate, 3-[(3-methacryloylaminopropyl)dimethylammonio]propane-1-sulfonate, 4-[(3-methacryloylaminopropyl)dimethylammonio]butane-1-sulfonate, 2-[[3-(methacryloylamino)propyl]dimethylammonio]ethylmethylphosphate, 2-[[3-(methacryloylamino)propyl]dimethylammonio]ethylethylphosphate (In the general formula (3), A represents O or NH, and R 1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group, or an acyl group; R 2 indicates a methyl group, an ethyl group, or an acyl group, "Polymer (ii)" indicates polymer (ii), and "*" indicates the bonding position with the substrate surface.

Citation Information

Patent Citations

  • Pollen adhesion-preventing woven fabric and product of the pollen adhesion-preventing woven fabric

    JP2003213541A

  • Irritation inhibitor for fibers, composition, treating method and low irritative fiber

    JP2004068174A

  • Pollen adsorption preventive agent

    JP2006002147A

  • Surface-hydrophilic polyolefin molding and method for producing the same

    JP2008133434A

  • Ultra-low fouling sulfobetaine and carboxybetaine materials and related methods

    JP2009508542A